Correlation between Levels of Serum Prolactin and Total Sialic Acids Concentrations in Fertile and Infertile Women - Tawfiq, Iqbal Naji (Al-Nahrain Journal of Science, 2013)
The aim of this study was investigating the correlation between elevation of Prolactin levels and the increase of the concentrations of total sialic acids. The study was performed on 149 women consisted of 93 infertile hyperprolactinimic women (patients), age ranged16-38 years old, and 56 normoprolactinemic women as a control group, 18-37 years old. Serum prolactin (PRL) and gonadotroph hormones (Follicle stimulating hormone FSH and Luteinizing hormone LH) were measured using enzymatic immunoassay (EIA) method, resorcinol method for serum total sialic acids (SIA). Patients were divided into four groups, each group represented the level of prolactin of infertile women as follow: G1= (21-30), G2= (31-40), G3= (41-50), and G4= (51-60) ng/mL. Serum PRL levels in the patients groups were significantly(P≤0.05) elevated compared to the normal women. Serum SIA, FSH and LH levels showed no significant differences (P≤0.05) in the groups 1, 2, 3, and 4 when compared to healthy women (control). There was no correlation between serum prolactin hormone levels and SIA levels in the control and patients women. In conclusion there was an elevation in PRL levels, not combined with elevation in SIA, FSH, and LH levels. There was no correlation between elevation of PRL levels and total sialic acids concentrations in control and patients women. Thus, sialic acid has no correlation with the fertility or infertility in the women.